Inflammatory and neuropathic pain conditions do not primarily evoke anxiety-like behaviours in C57BL/6 mice - Pitzer, Claudia; La Porta, Carmen; Treede, Rolf-Detlef; Tappe-Theodor, Anke (European journal of pain, 2019)
Background Chronic pain is often accompanied by comorbidities like anxiety and depression. The temporal correlations, as well as the underlying mechanisms of these reciprocal correlations, are unclear. Moreover, preclinical studies examining emotional behaviour are very controversial, and a chronological analysis of anxiety-like behaviour in mouse pain models considering both genders has not been performed so far. Methods We used several behavioural tests to assess and validate anxiety-like behaviour in complete Freund's adjuvant (CFA) and spared nerve injury (SNI) pain models in C57BL/6 mice. Among these were the elevated plus maze test, open field test, hole-board test and light-dark test. Additionally, we included a late stage analysis of depression-like behaviour using the forced swim test. All tests were applied once for each cohort of mice. Importantly, we used C57BL/6N mice of both genders; we investigated the effect of social isolation, the impact of pain induction to either the right or left hind limb and also investigated C57BL/6J mice. Results The validity of test conditions was confirmed using the anxiogenic drugs Yohimbine and Pentylenetetrazol. Anxiety-like behaviour was analysed throughout the time period when mice exhibited hypersensitivity to mechanical stimuli. We did not observe any consistent alteration in anxiety-like behaviour at any of the investigated time points between 1 and 14 days following CFA-induced inflammation or 3 and 84 days following SNI surgery using different behavioural tests. Conclusions Inflammatory and neuropathic pain conditions do not primarily evoke anxiety- and depression-like behavioural alterations within the herein investigated time period. Significance Anxiety-like behaviour is not primarily altered following CFA and SNI in C57BL6 mice, irrespective of the gender, mouse sub-strain, housing conditions or affected body side within the herein investigated time period.
First published: 11 August 2018
Gesehen am 04.04.2019